Plato's Creative Imagination: (Re)Membering the Chora(l) Love that We Are. (September 2019) - Lynch-Lawler, Cheryl
The Platonic chora, as the third, intermediating term, has been left in a state of virtual dereliction in the West. Its ternary logic transmutes oppositional logics of binarity, including the oppositions of interior and exterior, psyche and cosmos, human and divine. In this article I (psycho)analyse the mytho-philosophical trajectory of the chora from Plato's Timaeus, and Diotimaic love found in Plato's Symposium . I argue that both the disruptive force of Diotimaic love, and the subversive chora with its 'bastard reasoning' 1 are indicative of Plato's efforts to resolve an internalized conflict which mirrored a larger conflict found in his cultural epoch, a time in which abstracted self-consciousness was on the horizon and chthonic-participatory consciousness was receding. In (re)membering the chora I find a fecund space-time, an enabling field, for human participatory becoming-with the cosmos.